2016
DOI: 10.1167/iovs.15-18944
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Vessel Density in Healthy, Glaucoma Suspect, and Glaucoma Eyes

Abstract: PurposeThe purpose of this study was to compare retinal nerve fiber layer (RNFL) thickness and optical coherence tomography angiography (OCT-A) retinal vasculature measurements in healthy, glaucoma suspect, and glaucoma patients.MethodsTwo hundred sixty-one eyes of 164 healthy, glaucoma suspect, and open-angle glaucoma (OAG) participants from the Diagnostic Innovations in Glaucoma Study with good quality OCT-A images were included. Retinal vasculature information was summarized as a vessel density map and as v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
362
3
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 430 publications
(426 citation statements)
references
References 50 publications
26
362
3
6
Order By: Relevance
“…1,19,20 In the current study, the reduced VD in eyes with POAG agreed with the results of previous reports. [3][4][5] However, it is not clear if this phenomenon reflects reduced RPC density alone or includes thinning of the major retinal arteries in eyes with POAG. 21,22 Interestingly, the reduced VD was found in eyes with OH before any sign of GLV or cpNFLT damage, which was confirmed by multiple comparisons (P ¼ 0.018; Table 2) and the ROC curve (P ¼ 0.006; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,19,20 In the current study, the reduced VD in eyes with POAG agreed with the results of previous reports. [3][4][5] However, it is not clear if this phenomenon reflects reduced RPC density alone or includes thinning of the major retinal arteries in eyes with POAG. 21,22 Interestingly, the reduced VD was found in eyes with OH before any sign of GLV or cpNFLT damage, which was confirmed by multiple comparisons (P ¼ 0.018; Table 2) and the ROC curve (P ¼ 0.006; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some reports have been published on low vascular flow index (mean decorrelation) and peripapillary vessel density in glaucomatous eyes. [2][3][4] In previous optical coherence tomography angiography (OCTA) studies, the areas under the curve (AUCs) of the vascular flow index and vessel density ranged from 0.82 to 0.892 and 0.80 to 0.94, respectively. [2][3][4] Therefore, the OCTA parameters of vascular insufficiency might be useful for differentiating glaucomatous from normal eyes.…”
mentioning
confidence: 99%
“…The decreased microvascular density was more severe in the inferior region in eyes with more superior visual field (VF) defect and vice versa. Similarly, Yarmohammadi et al 22 and Chen et al 23 reported that the vessel density within the RNFL was lower in eyes with primary open-angle glaucoma (POAG) than in glaucoma suspects and healthy eyes. Akagi et al 24 showed that the parapapillary retinal vessel density was reduced in the corresponding hemi-field in POAG eyes with hemi-field VF defect.…”
mentioning
confidence: 93%
“…[2][3][4][5] Recent reports indicate that there is decreased optic disc perfusion and peripapillary capillary density on OCT angiography in patients with chronic glaucoma. 4,[6][7][8][9] This has led to speculation that reduced capillary density from OCT angiography in glaucoma eyes provides evidence for a primary role in the pathogenesis of glaucoma. However, as Schuman pointed out in his commentary on OCT angiography, "recently acquired OCT angiography images still do not answer the question of which comes first: changes in ocular blood flow or optic nerve injury?"…”
Section: Introductionmentioning
confidence: 99%